European Wool Carder Bee, Anthidium manicatum (Linnaeus) (Insecta: Hymenoptera: Megachilidae) - Samantha Gallagher; Andrea Lucky (EDIS, 2019)
This document provides an in-depth profile of the European wool carder bee, Anthidium manicatum. It covers the bee’s taxonomy, distribution, physical description, life cycle, and behavior. The document also discusses the bee’s nesting habits, host plants, and economic importance, highlighting its adaptability and potential impact on native species and ecosystems.